Sudden cardiac death of athletes and pre-participation screening: The youth league coach perspective - Akinci, Y.; Dursun, M. (International Journal of Applied Exercise Physiology, 2020)
After dosed physical load, 104 young men had a favourable type of response of heart rate and systolic blood pressurein the first minute of the recovery period. In 32 first-year students of Tyumen universities, hypotonic and hypertonic types of cardiovascular system reaction were detected, indicating low functional capabilities of central hemodynamics. This is due to the hypodynamia and hypokinesia that took place in connection with passing exams at school and entering University, as well as the emotional mood during the exams.